Targeted Metabolomic and Biochemical Changes During Nitrogen Stress Mediated Lipid Accumulation in Scenedesmus quadricauda CASA CC202 - Sulochana, Sujitha Balakrishnan; Arumugam, Muthu (Frontiers in Bioengineering and Biotechnology, 2020)
Scenedesmus quadricauda CASA CC 202, a potent freshwater microalga is being used as a biofuel feedstock, which accumulates 2.27 fold lipid during nitrogen stress induction. Upon nitrogen starvation, S. quadricauda undergoes biochemical and metabolic changes that perturb the cell to cope up the stress condition. The nitrogen stress-induced biochemical changes in mitochondrion exhibits due to the oxidative stress-induced Reactive Oxygen Species (ROS) generation at high membrane potential (Δψm). The predominant ROS generated during nitrogen starvation was H2O2, OH-, O2.- and to suppress them, scavenging enzymes such as peroxidase and catalase increased to about 23.16 mU/ml and 0.79 U/ml as compared to control (20.2 mU/ml, 0.19 U/ml). The targeted metabolic analysis showed, stress-related non-proteinogenic amino acids and energy equivalents elevated during the initial hours of nitrogen starvation. The nitrogen stress-triggered biochemical and metabolic changes along with other cellular events eventually lead to lipid accumulation in S. quadricauda.